PENGARUH MOTIVASI KERJA DAN LINGKUNGAN KERJA TERHADAP KINERJA KARYAWAN PADA PT KGS - Veny Nur Anisyah; Eraera Hia; Temmy Setiawan (Desanta Publisher, 2026)
The Influence of Work Motivation and Work Environment on Employee Performance at PT KGS. This study examines the partial and simultaneous effects of work motivation and work environment on employee performance. Using a quantitative associative approach with 90 respondents, the results show that work motivation and work environment have positive and significant effects on employee performance, both partially and simultaneously.